2014
DOI: 10.1108/cdi-09-2013-0114
|View full text |Cite
|
Sign up to set email alerts
|

The impact of work engagement and workaholism on well-being

Abstract: 2014),"The gendered trickle-down effect: How mid-level managers' satisfaction with senior managers' supervision affects line employee's turnover intentions", If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
167
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 190 publications
(221 citation statements)
references
References 73 publications
11
167
0
12
Order By: Relevance
“…Attention was mainly paid to the social processes created by interacting with external actors. Finally, one study found that organizational support and supervisor support were positively related to work engagement (Caesens et al, 2014), which in turn had positive effects on well-being, illustrating once again the complexity of the concepts involved.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Attention was mainly paid to the social processes created by interacting with external actors. Finally, one study found that organizational support and supervisor support were positively related to work engagement (Caesens et al, 2014), which in turn had positive effects on well-being, illustrating once again the complexity of the concepts involved.…”
Section: Resultsmentioning
confidence: 99%
“…Martinez et al (2013)Striving to obtain a school-work-life balance: the full-time doctoral studentUSA5 PhD studentsQualitative8. Caesens et al (2014)The impact of work engagement and workaholism on well-beingBelgium343 PhD studentsQuantitative9. Schmidt and Umans (2014)Experiences of well-being among female doctoral students in SwedenSweden12 PhD studentsQualitative10.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations